1978
DOI: 10.1111/j.2042-7158.1978.tb13323.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between spontaneously beating atria from control and streptozocin-diabetic rats

Abstract: Isolated spontaneously beating atria from streptozocin diabetic rats were compared with those from controls. Diabetic atria were found to have reduced rates, increased forces of contraction and reduced sensitivity to the inotropic effects of noradrenaline, isoprenaline, tyramine and calcium. Positive chronotropic responses to tyramine were also reduced but those to noradrenaline and isoprenaline were increased suggesting that tyramine releasable stores of noradrenaline were reduced. Elevation of glucose concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
16
3

Year Published

1981
1981
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 14 publications
(2 reference statements)
10
16
3
Order By: Relevance
“…These results agree with earlier reports using telemetric monitoring in Zucker-fatty rats [2,3,19]. This tendency was also observed in WBN/Kob diabetic rats and streptozotocin-diabetic rats [11,13]. Although autonomic neuropathy is a well-documented complication in diabetic patients, Van Buren et al [25] reported that the reduced HR in diabetic rats is not derived from autonomic nervous dysfunction.…”
Section: Discussionsupporting
confidence: 82%
“…These results agree with earlier reports using telemetric monitoring in Zucker-fatty rats [2,3,19]. This tendency was also observed in WBN/Kob diabetic rats and streptozotocin-diabetic rats [11,13]. Although autonomic neuropathy is a well-documented complication in diabetic patients, Van Buren et al [25] reported that the reduced HR in diabetic rats is not derived from autonomic nervous dysfunction.…”
Section: Discussionsupporting
confidence: 82%
“…This lower R in the atrium coincided with other results that the basal value of R in the right atrium decreased in the isolated myocardium of ex perimentally diabetic animals (7,9,18,22). On the other hand, in contrast to the present result, Fein et al (19) reported that the basal value of -dF/dt decreased more markedly than that of +dF/dt in the left ventricular papillary muscle of diabetic rats.…”
Section: Discussioncontrasting
confidence: 56%
“…The hearts of streptozotocin diabetic rats were shown to have abnormalities in left ventricular contraction and relaxation, 33 in relaxation of isolated papillary muscle, 34 and in the contraction and response to catecholamines of isolated atria. 35 Alloxan diabetic dogs were shown to have impaired cardiac function and an accumulation of cholesterol and triglyceride in the myocardium. 36 Evidence for decreased response to stress in the diabetic heart has come from studies of the effect of increasing ischemia on the development of cardiac failure in alloxan diabetic rats.…”
Section: Nonatherosclerotic Heart Disease In Diabetesmentioning
confidence: 99%